Impact of leptin on memory function and hippocampal structure in mild cognitive impairment. Issue 12 (11th August 2016) - Witte, A. Veronica; Köbe, Theresa; Graunke, Anders; Schuchardt, Jan Philipp; Hahn, Andreas; Tesky, Valentina A.; Pantel, Johannes; Flöel, Agnes
Abstract: Metabolic changes have been suggested to contribute to dementia and its precursor mild cognitive impairment (MCI), yet previous results particularly for the "satiety hormone" leptin are mixed. Therefore, we aimed to determine if MCI patients show systematic differences in leptin, independent of sex, adipose mass, age, and glucose and lipid metabolism, and whether leptin levels correlated with memory performance and hippocampal integrity. Forty MCI patients (20 females, aged 67 years ± 7 SD) were compared to 40 healthy controls (HC) that were pair‐wise matched for sex, age, and body fat. Memory performance was assessed using the auditory verbal learning test. Volume and microstructure of the hippocampus were determined using 3T‐neuroimaging. Fasting serum markers of leptin, glucose and lipid metabolism, and other confounding factors were assayed. MCI patients, compared with HC, showed lower serum leptin, independent of sex, age, and body fat ( P < 0.001). Glucose and lipid markers did not attenuate these results. Moreover, MCI patients exhibited poorer memory and lower volume and microstructural integrity within hippocampal subfields. While leptin and memory were not significantly correlated, mediation analyses indicated that lower leptin contributed to poorer memory through its negative effect on right hippocampus volume and left hippocampus microstructure. We demonstrated that MCI is associated with lower serum leptin independent of sex, age, body fat, glucose, and lipid metabolism. Our data further suggest that inefficient leptin signaling could partly contribute to decreases in memory performance through changes in hippocampus structure, a hypothesis that should now be verified in longitudinal studies. Hum Brain Mapp 37:4539–4549, 2016 . ©2016 Wiley Periodicals, Inc.